Unlocking New Potential in Educational Technology: Using Edutren Application to Increasing the Effectiveness of Student Evaluation - Nurdin Nurdin; Mochammad Devi Cahya Ruhimat; Rifan Shodikin; Song Xinling (Universitas Negeri Malang, 2025)
This study aims to describe the use of the Edutren application in more effective student evaluation activities, emphasizing the significant impact of information and communication technology (ICT) in education management. A qualitative approach of exploratory case study type was utilized, with data collection employing triangulation techniques. In the interviews, an in-depth interview model by Bingham (2023) was adopted, with five stages of data analysis. Purposive sampling was employed to select participants with 13 individuals including principals, teachers, dormitory guardians, education personnel, students, and student guardians, participating in the study. The result shows that: (1) the utilization of Edutren can be categorized into three distinct stages. The first stage involves data input, which is conducted by the owner of the Middle Account (MA). The second stage encompasses data processing, which is executed by Edutren's automation features and is subject to the contractual agreement between the school principal and the MA. The final stage pertains to the display of various data. (2) The findings indicated that Edutren has been effective in enhancing the efficacy of student evaluation activities. This is due to the fact that it provides an evaluation system that is accurate, and sustainable, fosters collaboration between schools and student guardians, is data-driven, and delivers real-time student progress reports on a daily basis. This facilitates the subsequent design of follow-up decisions by the school and guardians. This is a new key to the future of education technology. Three points to increasing the outcome for school management are recommended.